Study the effects of pressure on warpage of dumbbell plastics part in injection moulding machine. - Mohd , amran; Salmah, Siti; Zaki, M; Raja, Izamshah; Mohd , Hadzley; Sivarao, Subramonian; Mohd Shahir, Kasim; Mohd Amri , Sulaiman (2013)
The optimization of processing parameters on warpage of polypropylene (PP) in the application of injection moulding machine was studied. The appropriate parameters were adjusted to reduce the warpage defect on the tensile test specimen of dumbbell. The type of injection moulding machine used in this research is Arburg 420C 800-250C. Four parameters that have been investigated: injection pressure, clamping pressure, back pressure and holding pressure. A concept of design of experiment (DOE) has been applied using Taguchi method to determine the suitable parameters. It is found that the optimum parameters setting that have been obtained were injection pressure at 950 bar, clamping pressure at 600 kn, holding pressure at 700 bar and back pressure at 75 bar. The depreciation value of warpage minimum index in this experiment was decreased by 4.6% after confirmation run.